Sport Mega-Events and Displacement of Host Community Residents: A Systematic Review - Claudio M. Rocha; Zixuan Xiao (Frontiers Media S.A., 2022)
The aim of this study was to conduct a systematic literature review to understand how empirical data have informed the knowledge about the relationship between hosting sport mega-events and displacement of host community residents. Following the PRISMA protocol, we conducted a search of academic and gray literature in sport, social sciences, and humanities databases. We excluded conceptual papers, conference abstracts, and works that discuss urban transformation or displacement but are not related to sport events. We also excluded works that associate sport mega-events with urban transformations but are not related to resident displacement. From the initial 2,372 works reviewed, 22 met the inclusion criteria. In empirical studies, displacement of residents has been studied exclusively in the context of the Olympic Games, since Seoul 1988, but with a higher frequency in most recent Games (Beijing, London, and Rio). The gigantism and the sense of urgency created by the Olympic Games may explain why this event has been frequently associated with resident displacement. Findings showed that residents suffered either direct, forced evictions or indirect displacements. The selected studies show a contradiction between the discourse of sport mega-events guardians for supporting the United Nations Sustainable Goals (SDG) and the practice of human rights within host cities of such events.